In Vivo Evaluation of Controlled Release Bucoadhesive Tablet Formulations Containing Verapamil Hydrochloride - Özalp, Betül; Özalp, Koray (Fırat University, 2003)
Aim: The aim of this study was to investigate the in vivo effect of buccal bioadhesive tablets which have controlled release on increasing the bioavaibility and eliminating the first transit effect of verapamil. Material and method: Bioavailability of oral classic tablets and buccoadhesive tablets of verapamil have been compared in 7 normal subjects. Results: Buccal administration increases the bioavaibility by 1.3 folds compared with the oral route beside eliminating its first pass effect in great extend and it has been shown that buccal adhesive tablets positively affects the diastolic functions of the heart while having no effect on the systolic functions. Conclusion: The controlled release buccal bioadhesive tablets of verapamil might be an alternative in the therapy.

Amaç: Bu çalışmada, verapamilin ilk geçiş etkisinin ortadan kaldırılması ve biyoyararlanımın arttırılabilmesi için geliştirilen kontrollü salım yapan bukkal biyoadheziv tabletlerinin in vivo olarak incelenmesi amaçlanmıştır. Gereç ve yöntem: Verapamil içeren bukoadheziv tabletlerin biyoyararlanımı 7 sağlıklı gönüllüde klasik verapamil tableti ile mukayese edilerek incelenmiştir. Bulgular: Bukkal uygulamada oral yola göre biyoyararlanımın 1.3 kat arttığı ilk geçiş etkisinin büyük ölçüde ortadan kalkabileceği, bukoadheziv tablet kullanımı ile kalbin diastolik fonksiyonlarının olumlu yönde etkilendiği, sistolik fonksiyonların etkilenmediği bulunmuştur. Sonuç: Kontrollü salım yapan verapamil hidroklorür içeren bukkal biyoadheziv tabletler tedavide alternatif olabilir.
Verapamil Hidroklorür İçeren Kontrollü Salım Yapan Bukoadheziv Tablet Formülasyonlarının İn Vivo İncelenmesi